VD_FINDINFO Jug / 2016 / 249 vom 2. Februar 2016 - VD Tribunal cantonal (2016)
ABUS DE CONFIANCE, VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION, CONCOURS D'INFRACTIONS | 138 ch. 1 CP, 217 al. 1 CP, 49 al. 1 CP